Pengaruh Servicescape Dan Variasi Menu Terhadap Keputusan Pembelian Di Aroma Resto And Coffee Padang - Muli Junita; Hijriyantomi Suyuthie (Jurnal Manajemen Pariwisata dan Perhotelan, 2023)
This study aims to analyze the influence of servicescape and menu variations on purchasing decisions at Aroma Resto and Coffee Padang. This type of research is a causal associative survey method with quantitative data. The population of this study was consumers who visited Aroma Resto and Coffee Padang with a sample of 110 people, using techniques purposive sampling. The research instrument used questionnaires (questionnaires) arranged according to Likert scale. The data was analyzed using SPSS version 23.00 and the results of the analysis were presented in tabular form. The result of the study was servicescape (X1) on Aroma Resto and Coffee Padang in a good category with a percentage of 64%. Menu variation (X1) in Aroma Resto and Coffee Padang in good category with a percentage of 57.3%. The purchase decision (Y) on Aroma Resto and Coffee Padang is in a good category with a percentage of 62.7%. Multiple linear regression tests with T tests on servicescape variables and menu variations affect purchasing decision variables at Aroma Resto and Coffee Padang. The F test value of servicescape variables (X1) and menu variations (X2) affect simultaneously purchasing decisions at Aroma Resto and Coffee Padang. The Adj. R square value of 0.512 means that servicescape variables and menu variations have an effect of 51.2% on purchasing decisions at Aroma Resto and Coffee Padang and 48.8% are influenced by other variables.